Entropy convergence in early bilinguals’ syntactic packaging - Engemann, Helen (Frontiers in Psychology, 2022)
A core question in developmental and cognitive research concerns the way linguistic variation affects the acquisition process. Previous research on monolinguals suggests that children, but not adults, tend to regularize inconsistent input, resulting in reduced variation. Some recent claims explain regularization as a general bias linked to cognitive load. However, little is known about bilingual acquisition contexts where children naturally experience both increased variability and cognitive load. This study investigated the impact of between- and within-language variability in syntactic packaging (i.e., how semantic elements are mapped onto syntactic units) on simultaneous bilinguals’ acquisition of motion event encoding. In this domain, French is considered highly variable, in contrast to low variability demonstrated by English. Based on this crosslinguistic contrast, 96 English-French bilingual children (aged 4 to11 years) and 96 age-matched monolinguals of each language described 32 animated cartoons showing complex motion events. Children’s variability of selected syntactic patterns was measured using the information-theoretical concept of entropy. Results indicated that bilingual children significantly reduced syntactic variation relative to monolingual peers, but only in French, the more variable language. Moreover, bilingual children converged in entropy levels across the two languages and patterned mid-way between respective monolinguals. These findings suggest that the cognitive load inherent in bilingualism is not sufficient to explain reduced linguistic variation. Instead, the asymmetric drop in entropy highlights the strong impact of crosslinguistic differences and thus underlines the importance of taking language-specific factors into account in theories of cognitive load.